From School Gardens to Community Oases: Fostering Environmental and Social Resilience in Urban Spaces - Ioanneta Dimouli; Dimitra Koumparou; Spyridon K. Golfinopoulos (Geographies)
This case study in the municipality of Acharnes, Greece, examines a local initiative that transforms schoolyards into community gardens, involving teachers, pupils, parents, grandparents, and neighbors. The research explores participants’ perceptions of these transformations, with a focus on interactions with non-human beings such as pollinators. Data were collected using a questionnaire completed by 85 participants, including parents and guardians of pupils and school staff. Data analysis was conducted using statistical software to evaluate the research sample. Initially, descriptive statistics, including frequency distributions, were used to summarize the demographic and baseline variables of the sample. Next, Kendall’s tau correlation was applied to assess statistically significant relationships, such as those between age and proximity to green spaces, as well as gender, education, and green space preferences. The results of the survey reveal the “embrace” of these new urban green areas by both the school and the local community. This study, as part of an effort to address broader challenges in urban contexts, highlights the need for further in-depth exploration and examination of these dynamics to provide valuable insights into the design and management of school gardens. The aim is to enhance community engagement and urban biodiversity, with a central focus on social and environmental resilience.